The WIRELESS COMPUTER NETWORK MANAGEMENT SECURITY ANALYSIS - Setyantoro, Dwipo; Afifah, Vivi; Hasibuan, Rika Astuti; Aprilia, Novi; Sari, Novi Permata (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
The use of a wireless computer network in some institutions has become a very flexible option to connect all users of the existing computer network in the institution. This flexibility also has the disadvantage that anyone with a network password can take advantage of the wireless network. The possibility of threats to information security is very large, such as the presence of intruders on the network. Therefore, it is necessary to manage wireless networks that pay attention to information security issues on the network. The Directorate General of New, Renewable Energy and Energy Conservation at the Ministry of Energy and the Human Resources Republic of Indonesia was chosen as the research location given that computer network users in this institution are diverse and have also used The Dude MikroTik application to manage wireless computer networks, which are instruments to analyze information security. in this institution. The analysis was conducted to identify the activities and effectiveness of information security management in this institution. This study concludes that the use of The Dude MikroTik application is quite helpful in analyzing information security on wireless computer networks in this institution.